Safety and acceptability of vaginal disinfection with benzalkonium chloride in HIV infected pregnant women in west Africa: ANRS 049b phase II randomized, double blinded placebo controlled trial. DITRAME Study Group. Issue 6 (1st December 1999) - Msellati, P; Meda, N; Leroy, V; Likikouët, R; Van de Perre, P; Cartoux, M; Bonard, D; Ouangre, A; Combe, P; Gautier-Charpentier, L; Sylla-Koko, F; Lassalle, R; et al.
Abstract : OBJECTIVES: To study the tolerance and acceptability in Africa of a perinatal intervention to prevent vertical HIV transmission using benzalkonium chloride disinfection. DESIGN: A randomized, double blinded phase II trial. SETTING: Prenatal care units in Abidjan (Côte d'Ivoire) and Bobo-Dioulasso (Burkina Faso). PATIENTS: Women accepting testing and counselling who were seropositive for HIV-1 and under 37 weeks of pregnancy were eligible. A total of 108 women (54 in each group) enrolled from November 1996 to April 1997, with their informed consent. INTERVENTION: Women self administered daily a vaginal suppository of 1% benzalkonium chloride or matched placebo from 36 weeks of pregnancy, and a single intrapartum dose. The neonate was bathed with 1% benzalkonium chloride solution or placebo within 30 minutes after birth. MAIN OUTCOME MEASURES: Adverse events were recorded weekly, with a questionnaire and speculum examination in women through delivery, and examination of the neonate through day 30. The incidence of genital signs and symptoms in the women and cutaneous or ophthalmological events in newborns were compared between groups on an intent to treat basis. RESULTS: The median duration of prepartum treatment was 21 days (range 0-87 days). Compliance was 87% for prepartum and 69% for intrapartum treatment, and 88% for the neonatal bath, without differences between the two groups. In women, the most frequent event was leucorrhoea; the incidence of adverse events did not differ between treatment groups. In children, the incidence of dermatitis and conjunctivitis did not differ between the benzalkonium chloride and placebo groups (p = 0.16 and p = 0.29, respectively). CONCLUSION: Vaginal disinfection with benzalkonium chloride is a feasible and well tolerated intervention in west Africa. Its efficacy in preventing vertical HIV transmission remains to be demonstrated.